Ferrocene-containing optically active liquid-crystalline side-chain polysiloxanes with planar chirality - Brettar, Julie; Burgi, Thomas; Donnio, Bertrand; Guillon, Daniel; Scharf, Toralf; Deschenaux, Robert (My University, 2006)
Optically active liq.-cryst. side-chain polysiloxanes have been prepd. by grafting planar chiral ferrocene-based vinyl monomers onto com. available polyhydrosiloxane. Two ferrocene monomers have been synthesized: a linear-type monomer, which displays a monotropic chiral smectic C (SC*) phase and enantiotropic smectic A (SA) and chiral N (N*) phases, and a laterally branched monomer, which shows an enantiotropic N* phase. X-ray diffraction anal. indicates a monomol. organization of the monomeric units within the smectic layers. The polymers retain the liq.-cryst. phases of their corresponding monomers. The UV-vis and CD (CD) spectra are in agreement with the structure of the monomers and polymers. The molar absorption coeff. (?) and molar circular dichroic absorption coeff. (??) values of the polymers are proportional to the no. of monomeric units grafted onto them. The abs. configuration of the ferrocene carboxylic acid intermediate, used to synthesize the monomers, has been detd. on the basis of CD spectra. The helical twisting power (HTP) of the nematogenic monomer and polymer have been detd. in E7, and indicate that such materials could be used as chiral dopants. Finally, this study demonstrates that the nature of chiral phases can be controlled by structural engineering of the org. groups only, with ferrocene acting as the source of chirality. [on SciFinder(R)]